Assessment of Medication usage in Geriatric Wards in a Teaching Hospital - Khan, Zakir; Khan, Junaid; Zafar, Shaista; Khan, Asghar; Khan, Faiz Ullah; Kamran, Sohail; Kamran, Muhammad; Jamal, Muhammad Nasir; Khan, Bazgha (Indian Journal of Pharmacy Practice)
Introduction: Evaluation of medication usage pattern is crucial for the better patient care, particularly for the geriatric who often have experience with multiple therapy and problems. This study was conducted to investigate the medication usage in elderly patients through a validated World Health Organization (WHO) indicators. Methods: A retrospective crossectional and non-interventional study was conducted in the geriatric outpatient departments in a teaching hospital (Islamabad, Pakistan). The patients aged ≥60 years visiting the geriatric medical outpatient and emergency department from September 2018 to April 2019 were selected through random systematic sampling technique. The collected information was evaluated according to the WHO recommendations. Results: A total of 3,792 drugs were prescribed (average drug per prescription= 5.2 (Range 4-8) in 720 elderly patients. Out of these, antimicrobials were prescribed in 76.4% (n=550), at least one injectable medication in 63.9% (n=460), generic prescribing in 30% (n=1141) and prescribing from National essential list/hospital formulary in 95.8% (n=3634) of the prescription. A statistically significant difference was observed between prescribing practices and WHO optimal values (P<0.001). The most frequently prescribed class of antimicrobials was cephalosporins (65.3%) and ceftriaxone (41%), ciprofloxacin (13.6%) and cefuroxime (10.7%) were the most commonly used antibiotics. Conclusion: The major problems identified in this study were polypharmacy, low generic prescribing, higher usage of antimicrobials and injectable. A special attention is required by the healthcare authorities for the better care of the geriatric patients.
Keywords: Geriatrics; Antimicrobials; Audit; Health care; Outpatient; Pakistan.